2003
DOI: 10.1053/jhep.2003.50051
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of cellular immune response against hepatitis C virus nonstructural protein 3 by cationic liposome encapsulated DNA immunization

Abstract: A vaccine strategy directed to increase Th1 cellular immune responses, particularly to hepatitis C virus (HCV) nonstructural protein 3 (NS3), has considerable potential to overcome the infection with HCV. DNA vaccination can induce both humoral and cellular immune responses, but it became apparent that the cellular uptake of naked DNA injected into muscle was not very efficient, as much of the DNA is degraded by interstitial nucleases before it reaches the nucleus for transcription. In this paper, cationic lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 52 publications
2
31
0
1
Order By: Relevance
“…(16,27,77). Induction of potent Th1 responses by cationic liposomes (5,24) is consistent with our findings that mice vaccinated with gp63 in liposomes exhibited striking enhancements of the frequency and production of IFN-␥ from CD4 ϩ T cells both before infectious challenge and at 10 days or 12 weeks after infectious challenge. Significant frequencies of antigen-specific CD8 ϩ IFN-␥ ϩ cells were demonstrable only in the protected mice challenged 12 weeks after vaccination, supporting the idea of the importance of CD8 ϩ T cells in mediating long-term immunity (16,53).…”
Section: Cd4supporting
confidence: 88%
See 1 more Smart Citation
“…(16,27,77). Induction of potent Th1 responses by cationic liposomes (5,24) is consistent with our findings that mice vaccinated with gp63 in liposomes exhibited striking enhancements of the frequency and production of IFN-␥ from CD4 ϩ T cells both before infectious challenge and at 10 days or 12 weeks after infectious challenge. Significant frequencies of antigen-specific CD8 ϩ IFN-␥ ϩ cells were demonstrable only in the protected mice challenged 12 weeks after vaccination, supporting the idea of the importance of CD8 ϩ T cells in mediating long-term immunity (16,53).…”
Section: Cd4supporting
confidence: 88%
“…Cationic liposomes have been shown to markedly potentiate activation of immune response to plasmid DNA and oligonucleotides (24,75). More recently, the induction of cell-mediated immune response to poorly immunogenic protein and peptide antigens has been made possible through the use of positively charged liposome carriers (5,44).…”
mentioning
confidence: 99%
“…With respect to the NS3 protein of HCV, which has been evaluated in many laboratories as a therapeutic vaccine candidate, 7,8,13,23,34,35 some important findings have recently been made. The NS3 protein has three enzymatic functions in the viral life cycle.…”
Section: Discussionmentioning
confidence: 99%
“…They were also shown to stimulate humoral as well as cell-mediated immune responses and are therefore considered as potential adjuvants for protein-based or DNA-based vaccines [2][3][4][5][6][7]. In this context, we previously demonstrated that mice injected with diC14-amidine (3-tetradecylamino-tert-butyl-N-tetradecylpropionamidine) cationic liposomes combined with a recombinant allergen (Der p 1) developed a Th1-biased immune response and were protected against subsequent induction of a Th2-type allergen-specific response [8].…”
Section: Introductionmentioning
confidence: 99%